Two new species of Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Montenegro - Kolimár, Robert; Hlaváč, Peter; Baňař, Petr (Zootaxa, 2024)
Two new species of the genus Bryaxis Kugelann, 1794, Bryaxis duboki sp. nov. and Bryaxis biogradensis sp. nov. from Montenegro are described and illustrated.